Models of school-family partnerships: the Malaysian context - Wee, Jennifer Beng Neo; Md. Nor, Sharifah; Kasa, Zakaria; Foo, Say Fooi (Universiti Putra Malaysia Press, 2001)
This study examined the headmasters' and teachers' perceptions towards the concepts, importance and school practices in parental involvement in order to identify the partnership models that existed in primary schools. Five hundred and fifty three respondents answered the questionnaires. The findings showed that the respondents' perceptions of the concepts of partnerships were partial. Majority of them perceived that parental involvement was important in the children's education especially for the children's cognitive, emotional, and social development. The findings also showed that only a few school practices in parent involvement were carried out. A few partnership models were adopted by the schools but these models were partial partnership models. The findings suggest that a holistic partnership requires schools to adopt a comprehensive model where parental involvement should extend from home-based activities to school-based activities.